2015
DOI: 10.1111/jnu.12155
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Symptom Science Through Use of Common Data Elements

Abstract: Background Use of common data elements (CDEs), conceptually defined as variables that are operationalized and measured in identical ways across studies, enables comparison of data across studies in ways that would otherwise be impossible. Although healthcare researchers are increasingly using CDEs, there has been little systematic use of CDEs for symptom science. CDEs are especially important in symptom science because people experience common symptoms across a broad range of health and developmental states, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 24 publications
(22 reference statements)
0
72
1
Order By: Relevance
“…The use of common data elements (CDEs) makes certain that a construct is consistently measured across studies both conceptually and operationally. 38 It is also recommended that symptoms should be consistently measured across disciplines. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The use of common data elements (CDEs) makes certain that a construct is consistently measured across studies both conceptually and operationally. 38 It is also recommended that symptoms should be consistently measured across disciplines. 39 …”
Section: Discussionmentioning
confidence: 99%
“…While the network approach to mood symptoms has received recognition in recent years, primarily in psychology and most recently in psychiatry (Fried et al, ), it has not to our knowledge reached nursing research. Better understanding and management of adverse health symptoms, including psychological distress, is recognized as a priority for nursing studies (Henly, ; Redeker et al, ), and a focus on depressive symptoms has been recognized as one of the core dimensions by the National Institute of Nursing Research through their symptom science agenda (Lee, Meek, & Grady, ). In this paper, we aim to advance the field of symptom‐focused studies in nursing research via a conceptual and empirical introduction of symptoms network analysis.…”
Section: Mental Disorders As Network Of Interacting Symptomsmentioning
confidence: 99%
“…Culture (Moser et al, 2014;Park & Johantgen, 2016), language, reading level, aging, sex, and developmental level (Schaakxs et al, 2017), among other factors, influence how symptoms and self-management are reported and measured (Redeker et al, 2015). Factors such as aging, race, sex, and gender may also influence biomarkers, genes, and gene expression.…”
Section: Challenges To the Use Of Biological Common Data Elements Formentioning
confidence: 99%